Analysis of Constraints and Solutions in Implementation Project-Based Learning (PJBL) Model in the Subject of Biology in Class X of SMA Negeri 1 Binjai - Dewi Portuna; Mardhiyah Riswan Hsb; Risfina Dwi Nanda; Halim Simatupang; Widya Arwita (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
Study This aim For identify problem main in Project- Based implementation Learning (PJBL) in subjects Biology in class X SMA Negeri 1 Binjai . Focus main study is limitations time and difficulty Teacher in manage class . Method used is descriptive with data collection via questionnaires and interviews with two Teacher biology . Results study show that available time No Enough For complete project tasks and difficulties in manage class hinder effectiveness of PJBL. For overcome problem this, recommended adjustment timetable lessons and training management class for Teacher. Implementation solution This expected can increase quality learning Biology through PJBL at SMA Negeri 1 Binjai .